Development of the E-Lintar Mobile App with Integrated Songs on Fifth Graders' Understanding of Food Chains - Barokah, Annisa Khoirul; Sutikno, Putri Yanuarita (Jurnal Pendidikan MIPA, 2025)
This study was motivated by students' challenges in understanding learning concepts in food chain material, which is often considered abstract and filled with new terms that are difficult to understand. Difficulties in distinguishing the roles of producers, consumers, and decomposers, as well as remembering the flow of the food chain, are the main obstacles for students. The objective of this study is to develop and evaluate the effectiveness of the E-Lintar Mobile App with integrated songs as an interactive, engaging, effective, and enjoyable learning medium that can enhance students' understanding of the taught material, thereby improving learning outcomes. This study employed the Research and Development (R&D) method with the ADDIE model, with 30 fifth-grade students as the subjects. Data collection was conducted through tests and non-tests, then analyzed using normality tests, t-tests, and N-Gain calculations. The results showed that this application is highly feasible for use, with a feasibility rating of 95% from subject matter experts, 94% from media experts, 98.75% from teachers, and 96.09% from students. The effectiveness of the application was proven through a t-test on a small group with a significance value (2-tailed) of 0.000 < 0.05, while on a large group with a significance value (2-tailed) of 0.000 < 0.05, the results showed a significant difference between the pretest and posttest results. The N-Gain test results for the small group were 0.7207, categorized as high, while the large group achieved 0.7518, also categorized as high. This study contributes to the innovation of technology-based learning media that supports students' critical thinking skills and facilitates teachers in integrating multimedia. Thus, the E-Lintar Mobile App with integrated songs supports concept understanding, improves memory, and creates a more engaging and interactive learning environment for science education, particularly on the topic of food chains at the elementary school level.      Keywords: e-lintar mobile app, songs, sience, problem-based learning.